Oh, My Quad: A Clinical Commentary And Evidence-Based Framework for the Rehabilitation of Quadriceps Size and Strength after Anterior Cruciate Ligament Reconstruction. - Braidy Solie; Mitchell Carlson; Christopher Doney; Michael Kiely; Robert LaPrade (International Journal of Sports Physical Therapy)
Quadriceps weakness after anterior cruciate ligament reconstruction (ACLR) is a well-known phenomenon, with more persistent quadriceps weakness observed after ACLR with a bone-patellar tendon-bone or quadriceps tendon autograft than with a hamstring tendon autograft. Longstanding quadriceps weakness after ACLR has been associated with suboptimal postoperative outcomes and the progression of radiographic knee osteoarthritis, making the recovery of quadriceps size and strength a key component of ACLR rehabilitation. However, few articles have been written for the specific purpose of optimizing quadriceps size and strength after ACLR. Therefore, the purpose of this review article is to integrate the existing quadriceps muscle basic science and strength training literature into a best-evidence synthesis of exercise methodologies for restoring quadriceps size and strength after ACLR, as well as outline an evidence-informed quadriceps load-progression for recovering the knee’s capacity to manage the force-profiles associated with high-demand physical activity.